Characterization of the Evolution of Energy Loss Rate in Cyclic Load Testing of Marine Soft Soil - Yindong Sun; Heng Zhang; Yajun Liu; Ke Wu; Yang Zheng (Applied Sciences)
The study of energy evolution laws has been widely applied in the geotechnical analysis of soft rocks and coal seams. However, research on marine soft soil has primarily focused on consolidation behavior, shear properties, and microstructural evolution, with limited exploration of systematic methods based on energy evolution laws. This paper addresses this gap by analyzing dynamic triaxial test data to explore the relationship between energy loss rate and the number of cyclic loadings in marine soft soil. Through energy loss calculations and derivations, a mathematical expression for the energy loss rate is established using curve fitting. Additionally, an envelope diagram depicting the energy dissipation rate of marine soft soil under varying perimeter pressures and water contents is presented. This diagram serves as a criterion for assessing the stability of marine soft soil, which is further validated through engineering applications. The findings offer novel approaches and insights for developing theoretical models and rapid strength assessment techniques for marine soft soil in engineering practices.